A patterned high-reflective layer with good adhesion and its preparation method and application

By adopting a multi-layer structure design in the high-reflective layer, including surface-modified glass substrate, n(Si/W) layer, gradient W-Cr alloy layer, etc., the problem of insufficient adhesion of the high-reflective layer is solved and high-reflective layer is achieved. The combination of reflectivity and good adhesion significantly improves the mechanical and optical properties of the structure.

CN118957528BActive Publication Date: 2025-01-24CHANGSHA SHAOGUANG CHROME BLANK +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411451985.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing high-reflective layers have insufficient adhesion performance and are prone to peeling, especially in high temperature or humid and heat environments, which leads to a degradation of reflective performance.

Method used

Adopt a multi-layer structure design from bottom to top, including surface modified glass substrate, N (Si/W) layer, gradient W-CR alloy layer, CR layer, silicon dioxide layer, and graphic reflection layer. Control the thickness, ingredients and interface structures of each layer to achieve a combination of high reflectivity and good adhesion.

Benefits of technology

Significantly improves the adhesion and optical properties of the highly reflective layer, enhances the mechanical and thermal stability of the structure, reduces interface stress, and improves the reliability and durability of the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118957528B_ABST
    Figure CN118957528B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thin film materials, and provides a patterned high-reflection layer with good adhesion, a preparation method and an application thereof, wherein the high-reflection layer comprises an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer and a patterned reflective layer which are sequentially located on a surface-modified glass substrate from bottom to top; the n(Si / W) layer is composed of n periods of alternate deposition of Si layers and W layers, wherein the alternating period n is 30-50; the W content of the gradient W-Cr alloy layer gradually decreases and the Cr content gradually increases in a direction away from the n(Si / W) layer; the high-reflection layer of the invention realizes the combination of high reflectivity and good adhesion, solves the problems of easy peeling and poor stability of traditional high-reflection layers, and has a wide range of application value in the fields of photolithography masks, optical systems and semiconductor manufacturing, and provides a new technical path for the development of high-performance optical components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thin film materials, and in particular to a patterned high-reflective layer with good adhesion, a preparation method and application thereof. Background Art

[0002] As a key component in the optical system, the high reflective layer plays a vital role in the fields of photolithography masks, semiconductor manufacturing, lasers, and precision optical instruments. These application scenarios place stringent requirements on the performance of the high reflective layer, requiring not only excellent reflectivity and optical stability, but also good adhesion and durability to adapt to complex working environments and long-term use requirements. Especially in the semiconductor manufacturing process, the high reflective layer needs to withstand frequent thermal cycles and chemical corrosion while maintaining high-precision optical properties. Therefore, the development of a high reflective layer with excellent adhesion is of great significance for improving the reliability and service life of optical components, reducing maintenance costs, and improving production efficiency. In addition, with the advancement of micro-nano processing technology, new requirements have been put forward for the graphical design of high reflective layers, which can not only realize more complex optical functions, but also provide greater design freedom for the development of new optoelectronic devices, thereby promoting technological innovation and upgrading of related industries.

[0003] However, the current high-reflection layer technology still faces many challenges in meeting the above performance requirements. Traditional high-reflection layers often have problems with insufficient adhesion and easy peeling, which seriously affects the reliability and service life of optical components. For example, the Chinese patent with publication number CN113267956A discloses a high-reflectivity multilayer film, but it is prone to interlayer peeling under high temperature or humid heat environment, resulting in decreased reflective performance. These shortcomings are mainly due to factors such as unreasonable multilayer film structure design, improper interface stress control, and inappropriate material selection. Therefore, the development of a high-reflection layer with both good adhesion and fine graphic capabilities has important practical significance and application value for solving the limitations of existing technologies and meeting the needs of advanced optical systems. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a patterned high-reflective layer with good adhesion and a preparation method and application thereof, so as to solve the problem that the current high-reflective layer has insufficient adhesion performance.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A patterned high-reflection layer with good adhesion, the high-reflection layer comprising an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer, and a patterned reflective layer, which are sequentially located on a surface-modified glass substrate from bottom to top;

[0009] The n(Si / W) layer is composed of n cycles of alternate deposition of Si layer and W layer, wherein the alternating cycle n is 30-50; the bottom layer of the n(Si / W) layer is a Si layer connected to the surface-modified glass substrate, and the top layer is a W layer; the thickness of the Si layer is 3-8 nm, the thickness of the W layer is 3-8 nm, and the thickness ratio of the Si layer to the W layer is 1:1; the interface between the Si layer and the W layer is a wavy interface;

[0010] The gradient W-Cr alloy layer has a W content that gradually decreases and a Cr content that gradually increases in a direction away from the n(Si / W) layer;

[0011] The surface-modified glass substrate is an oxygen plasma surface-modified glass substrate; the average surface roughness of the oxygen plasma surface-modified glass substrate is 0.15-0.45 nm;

[0012] The method for surface modification of a glass substrate by oxygen plasma comprises the following steps:

[0013] 1) Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol in sequence using an ultrasonic cleaner, and then dried completely in a vacuum drying oven at room temperature;

[0014] 2) Surface modification of glass substrate: The glass substrate obtained by step 1) is surface modified by oxygen plasma; the process parameters of the oxygen plasma surface modification are: at a pressure of 1.0-2.0 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 50-80 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 70-80 W, and the sputtering time is 250-350 s.

[0015] The present invention adopts the design of periodic Si / W multilayer film mainly to enhance the optical performance and structural stability of the high reflective layer. Through the carefully designed n (Si / W) layer structure, the present invention realizes the organic combination of high reflectivity and good adhesion. The periodic structure of alternating deposition of Si layer and W layer is the core of the design. By controlling the alternating period n between 30 and 50, the optical properties of the high reflective layer can be effectively adjusted. This periodic structure makes full use of the complementary advantages of Si and W materials. The Si layer has good interface bonding and stress buffering ability, while the W layer provides excellent reflective performance and mechanical strength. The present invention achieves not only the optimization of optical performance but also ensures the balance and stability of the overall structure by precisely controlling the thickness of the Si layer and the W layer within the range of 3 to 8nm and maintaining the thickness ratio of the two layers at 1:1.

[0016] The present invention adopts the design of gradient W-Cr alloy layer mainly to enhance the overall performance and structural stability of the high-reflection layer. This innovative technical solution achieves the synergistic improvement of multiple key performances by introducing a carefully designed transition layer between the n(Si / W) layer and the Cr layer. The core feature of the gradient W-Cr alloy layer is the gradual change of its composition. From the n(Si / W) layer to the Cr layer, the W content gradually decreases, while the Cr content gradually increases, forming a continuously changing alloy structure. This gradient-designed W-Cr alloy layer provides a wide range of adjustment space for achieving optimal performance. By controlling the ratio of W and Cr, different physical and chemical properties can be achieved at different depths, thereby optimizing the performance of the entire high-reflection layer.

[0017] The design of the gradient W-Cr alloy layer plays multiple key roles in the entire high-reflection layer structure. First, it provides a smooth transition from the n(Si / W) layer to the Cr layer, effectively reducing the interface stress and lattice mismatch, and enhancing the mechanical stability of the entire structure. This gradient structure can alleviate the difference in thermal expansion coefficients between different materials and improve the reliability of the high-reflection layer in a temperature-changing environment. Second, the gradient alloy layer significantly enhances the adhesion between the layers. By gradually changing the ratio of W and Cr, the chemical composition gradient from the n(Si / W) layer to the Cr layer is achieved, avoiding the bonding problems that may be caused by the abrupt interface. This design not only improves the mechanical strength of the entire structure, but also enhances its anti-peeling and impact resistance. In addition, the gradient W-Cr alloy layer may also have a positive impact on the optical properties of the entire high-reflection layer. It is worth noting that the design of the gradient W-Cr alloy layer forms a good synergistic effect with the entire high-reflection layer structure. It not only achieves seamless connection with the underlying n(Si / W) periodic structure and the upper Cr protective layer, but also works together with the surface-modified glass substrate to form a multilayer structure with comprehensive performance. The surface-modified glass substrate provides a stable foundation for the entire structure; the n(Si / W) layer achieves high reflectivity; the gradient W-Cr alloy layer enhances adhesion and reduces stress; and the Cr layer provides protection and possible graphical properties. In general, the present invention successfully solves the interface problem between different functional layers in the high-reflectivity layer by adopting a gradient W-Cr alloy layer design, combined with precise composition control and advanced preparation technology. This innovative solution not only improves the mechanical stability and optical performance of the entire structure, but also enhances its reliability and durability in complex environments. The collaborative design of this multi-layer structure provides a new technical path for the development of high-performance optical components, and is expected to play an important role in high-demand application fields such as precision optical instruments, laser systems, aerospace, etc.

[0018] The present invention adopts the design of silicon dioxide layer and patterned reflective layer mainly to enhance the functionality and application flexibility of the high reflective layer. This innovative technical solution realizes the fine control of optical performance and the possibility of patterned design by introducing silicon dioxide layer and patterned reflective layer on the high reflective layer, further improving the comprehensive performance of the whole structure.

[0019] The present invention adopts the design of wavy interface mainly to enhance the mechanical properties of Si / W multilayer film. The technical solution effectively improves the overall mechanical properties of the multilayer film by forming a special wavy interface structure between the Si layer and the W layer. The formation of the wavy interface originates from the island growth mechanism of the film during magnetron sputtering. This growth mode makes the interface have certain ups and downs, thus producing wavy morphological characteristics. This unique interface structure optimizes the mechanical properties of Si / W multilayer film in many aspects: first, the wavy interface increases the connection area between the Si layer and the W layer, strengthens the bonding force between the layers, and improves the mechanical strength and anti-peeling ability of the multilayer film; secondly, this interface structure can relieve interlayer stress to a certain extent and improve the structural stability of the multilayer film under high temperature or external force; thirdly, the wavy interface may affect the movement and propagation of dislocations, thereby enhancing the plastic deformation ability and toughness of the multilayer film; in addition, this interface structure may also change the crack propagation path and improve the fracture toughness of the multilayer film. It is worth noting that the Si layer and the W layer form a unique spatial structure at the wavy interface, which may produce a synergistic effect, such as forming a special stress distribution state or a dislocation blocking mechanism, thereby regulating the mechanical properties of the multilayer film at a microscopic scale. Through the design of the wavy interface, the interaction between the Si layer and the W layer is optimized, so that the entire multilayer film structure exhibits better mechanical properties, including higher hardness, better fatigue resistance and stronger impact resistance. In general, the present invention achieves a comprehensive improvement in the mechanical properties of Si / W multilayer films through a carefully designed wavy interface structure, and provides new ideas and methods for optimizing the mechanical properties of high-performance thin film materials. In general, the present invention achieves a comprehensive balance of high reflectivity, good adhesion, excellent thermal stability and long-term reliability through the sophisticated design of the n(Si / W) layer, providing a new technical solution for the field of high-performance optical coatings, and is expected to play an important role in optical applications in various harsh environments. The design of the glass substrate modified by oxygen plasma in the present invention is mainly used to enhance the adhesion performance of the high-reflectivity layer. This design effectively improves the surface activity of the glass substrate while maintaining its surface flatness through a carefully controlled plasma treatment process, laying a good foundation for the subsequent deposition of a high-reflection layer. Under specific pressure, gas ratio and RF power conditions, a large number of active groups, such as silicon oxygen radicals, are generated. This significantly improves the bonding force between the subsequent deposited layer and the substrate. At the same time, by precisely controlling the plasma treatment time, the present invention successfully strikes a balance between increasing surface activity and maintaining a low average surface roughness. This low-roughness surface property is crucial to ensuring the optical performance of the high-reflection layer because it reduces light scattering and improves reflection efficiency. In addition, the modified glass surface also has better chemical stability and uniformity, which helps the subsequently deposited n (Si / W) layer to form a more regular and stable structure.Through this surface modification treatment, the present invention not only improves the mechanical strength and durability of the entire high-reflection layer system, but also creates favorable conditions for achieving high-quality optical performance. It is worth noting that this surface modification technology forms a good synergistic effect with the subsequent multilayer structure design. The modified glass surface provides an ideal growth substrate for the n(Si / W) layer, promotes the formation of a wavy interface, which further enhances the interlayer bonding force and helps to reduce interface stress. At the same time, it also creates favorable conditions for the deposition of gradient W-Cr alloy layers and Cr layers, ensuring the stability and consistency of the entire multilayer structure. In general, the present invention successfully optimizes the surface properties of the glass substrate through precisely controlled oxygen plasma surface modification technology, lays a solid foundation for achieving high-performance, high-adhesion patterned high-reflection layers, and demonstrates the important role of material design and surface engineering in the manufacture of advanced optical components.

[0020] Preferably, the average amplitude height of the wavy interface is 0.5-1.6 nm, and the average width is 3.0-5.5 nm. The average amplitude height of the wavy interface is controlled within the range of 0.5-1.6 nm, and the average width is 3.0-5.5 nm. This precise size control enables the interface structure to maintain good interlayer bonding without excessively affecting the integrity of each single layer.

[0021] Preferably, the thickness of the gradient W-Cr alloy layer is 5-15 nm;

[0022] The thickness of the Cr is 20-60 nm;

[0023] The thickness of the silicon dioxide layer is 3 to 10 nm;

[0024] The patterned reflective layer is CrON, and its thickness is 2-12 nm.

[0025] The thickness of the gradient W-Cr alloy layer of the present invention is controlled within the range of 5 to 15 nm. This thin layer design can effectively play a transition role without significantly increasing the thickness of the entire structure. The preparation method using magnetron sputtering co-deposition of Cr target and W target can not only accurately control the composition and thickness of the alloy layer, but also ensure good film quality and uniformity. The selection of this preparation method reflects the pursuit of refined microstructure control and lays a technological foundation for realizing high-performance gradient alloy layers.

[0026] The silicon dioxide layer serves as a transition layer between the high reflective layer and the patterned reflective layer, and its thickness is controlled within the range of 3 to 10 nm. This thin layer design can not only effectively exert its function, but also minimize the impact on the thickness of the overall structure. The introduction of the silicon dioxide layer has multiple functions: first, it provides a stable growth substrate for the patterned reflective layer, which helps to form a higher quality and more uniform patterned reflective layer. Secondly, the silicon dioxide layer may have unique optical properties, such as a specific refractive index or scattering property, which helps to further optimize the optical performance of the entire structure. In addition, the silicon dioxide layer may also play a role in protecting the high reflective layer and enhancing the durability of the entire structure. The patterned reflective layer uses CrON material with a thickness of 2 to 12 nm. This design allows effective reflection regulation while keeping the overall structure thin. CrON are materials with excellent optical and mechanical properties, which can provide low reflectivity, high hardness and good chemical stability. In particular, the optical properties of these materials are in sharp contrast to the high reflective layer, making it possible to achieve a specific optical design. The graphic design of the reflective layer is a key innovation of the present invention. By forming a patterned reflective layer on the silicon dioxide layer, complex optical patterns or functional structures can be realized. This patterned design provides greater design freedom for optical components, making it possible to achieve precise control of high reflective and patterned reflective areas on the same substrate, thereby meeting the needs of more complex optical systems.

[0027] The multilayer structure design of the high reflective layer of the present invention embodies the synergistic effect between the components: the surface modified glass layer provides a stable foundation for the entire structure; the n(Si / W) layer achieves high reflectivity; the gradient W-Cr alloy layer enhances adhesion and reduces stress; the Cr layer provides protection; the silicon dioxide layer serves as a transition layer to optimize the interface characteristics; and the patterned reflective layer achieves local regulation of reflectivity. This synergistic effect enables the entire structure to have not only excellent optical properties, but also good mechanical properties, chemical stability and design flexibility. The introduction of the silicon dioxide layer and the patterned reflective layer forms a good complement to the entire high reflective layer structure. They not only achieve functional complementarity with the high reflective structure of the lower layer, but also provide new application possibilities for the entire optical element. For example, this design can be used to make high-performance optical elements such as reflectors, waveguide structures, optical filters, etc. with complex optical patterns. In general, the present invention successfully achieves fine regulation of optical performance by adopting the silicon dioxide layer and the patterned reflective layer design, combined with precise thickness control and material selection. This innovative solution not only improves the functionality and design flexibility of optical elements, but also provides the possibility for them to play a role in a wider range of application fields. This collaborative design of multi-layer structures has opened up a new technical path for the development of high-performance, multifunctional optical components, and promoted the innovation and progress of related technologies.

[0028] The present invention also provides a method for preparing a patterned high-reflective layer with good adhesion, comprising the following steps:

[0029] S1. Preparation of n (Si / W) layer: using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of the surface modified glass substrate, the number of alternating deposition cycles is n, and n (Si / W) layer is formed;

[0030] The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% is used as the target material, argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 25-40 sccm, the sputtering pressure is 0.15 Pa-0.35 Pa, the sputtering power is 100-145 W, the bias voltage is -50--100 V, and the substrate temperature is 130-160 ° C.

[0031] The preparation parameters of the W layer are as follows: W with a purity of 99.999% is used as the target material, argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 35~50sccm, the sputtering pressure is 0.15~0.35Pa, the sputtering power is 200~350w, the bias voltage is -30~-80V, and the substrate temperature is 150~190℃;

[0032] S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n (Si / W) layer;

[0033] Preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is adopted, a W target material with a purity of 99.999% and a Cr target material with a purity of 99.999% are used simultaneously, argon gas with a purity of 99.999% is used as a protective atmosphere, the argon gas flow rate is adjusted to 25-50 sccm, the initial sputtering power of the W target material is 100-150w, the sputtering power of the Cr target material is 30-50w, and the sputtering time is 5min. During the sputtering process, the sputtering power is adjusted once every 30s, the power of the W target material decreases linearly at a rate of 16-20w per minute, and the power of the Cr target material increases linearly at a rate of 24-30w per minute. Finally, the sputtering power of the W target material is 20-50w, and the sputtering power of the Cr target material is 150-200w. During the sputtering process, the rotation speed is 20-30rpm, the sputtering temperature is 150-200℃, and the sputtering pressure is 4 mTorr; The present invention realizes a gradual change in the W content and the Cr content in the W-Cr alloy layer by controlling the gradual change in the sputtering power of the W target and the Cr target;

[0034] S3. Preparation of Cr layer: Preparing a Cr layer on a gradient W-Cr alloy layer;

[0035] S4. Preparing a silicon dioxide layer: Preparing a silicon dioxide layer on the Cr layer;

[0036] S5. Preparing a patterned reflective layer: using a magnetron sputtering method to prepare a reflective layer to be patterned on the silicon dioxide layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer.

[0037] Preferably, the preparation parameters of the Cr layer in step S3 are: using magnetron sputtering method, using Cr with a purity of 99.95% as the target material, using 99.999% argon gas with a flow rate of 30-60 sccm as the atmosphere, sputtering power of 150-200w; deposition rate of 0.50-0.90 nm / s;

[0038] Preferably, the preparation parameters of the silicon dioxide layer in step S4 are: using magnetron sputtering technology, using quartz with a purity of 99.999% as a target material, using a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% at a flow rate of 30-60sccm as an atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 300-600w, the sputtering pressure is 0.5-1.5Pa, the bias voltage is -50--100V, and the substrate temperature is 100-150°C;

[0039] Preferably, the preparation parameters of the reflective layer to be patterned in step S5 are: using a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of 99.999% argon, 99.999% nitrogen and 99.999% oxygen with a flow rate of 25~50sccm as an atmosphere, wherein the volume ratio of argon, nitrogen and oxygen is 4:1:1, and the sputtering power is 300~600w.

[0040] The present invention can precisely control the thickness, composition and microstructure of each layer by strictly controlling the preparation parameters of each layer, such as sputtering power, gas flow rate, pressure, etc., so as to achieve fine adjustment of the overall performance. This highly controllable preparation process makes the technical solution have good repeatability and scalability, which is conducive to its application in industrial production. The layers show significant synergistic effects, and the fine adjustment of the overall performance is achieved by strictly controlling the preparation parameters.

[0041] The invention also provides an application of a patterned high-reflection layer with good adhesion in the fields of photolithography mask, optical system and semiconductor manufacturing.

[0042] (3) Beneficial technical effects

[0043] 1. The n(Si / W) periodic multilayer film structure of the present invention innovatively combines the characteristics of high reflectivity and good adhesion, and optimizes the optical performance and structural stability by precisely controlling the thickness and period number of the Si and W layers. The unique wavy interface enhances the interlayer bonding force, reduces the interface stress, and improves thermal stability and long-term reliability. The Si layer improves adhesion and stress distribution as a buffer layer, while the W layer provides excellent reflective performance and mechanical strength.

[0044] 2. The gradient W-Cr alloy layer design of the present invention innovatively solves the interface problem of the high reflective layer, significantly improving the overall performance and structural stability. Through the precise control of the W and Cr content ratio, a smooth transition from the n (Si / W) layer to the Cr layer is achieved, effectively reducing the interface stress and lattice mismatch. This gradient structure not only enhances the adhesion between the layers, but also improves the reliability of the structure in a temperature-changing environment. It forms a synergistic effect with the surface-modified glass substrate and the n (Si / W) layer, optimizing the optical performance and enhancing the mechanical strength.

[0045] 3. The present invention significantly improves the functionality and application flexibility of the high-reflection layer by introducing a silicon dioxide transition layer and a patterned CrON reflective layer. This innovative design allows precise control of high and low reflective areas on the same substrate to meet the needs of complex optical systems. The silicon dioxide layer provides a stable substrate for the patterned reflective layer and optimizes the interface properties; while the patterned CrON layer achieves local regulation of reflectivity and increases design freedom. The synergy between the layers not only ensures excellent optical performance, but also improves mechanical strength and chemical stability.

[0046] 4. The present invention significantly improves the adhesion and optical properties of the high reflective layer by using oxygen plasma to modify the glass substrate. The oxygen plasma surface modified glass substrate provides an ideal growth substrate for subsequent functional layers, and forms a good synergistic effect with the n(Si / W) layer, gradient W-Cr alloy layer, etc., promotes the formation of a wavy interface, enhances the interlayer bonding force, and reduces the interface stress. This innovative design not only improves the mechanical strength and durability of the overall system, but also optimizes the optical performance, reduces light scattering, and improves reflection efficiency.

[0047] 5. In the fields of photolithography masks, optical systems, semiconductor manufacturing, etc., the present invention can effectively solve the problems of easy peeling of traditional high-reflective layers and unstable optical performance, and provide a new solution for the technological progress of related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is an XRD phase analysis diagram of the surface-modified glass substrate prepared in Example 1 of the present invention and the n(Si / W) layer on the substrate.

[0049] Figure 2 This is a wavy interface morphology of the n(Si / W) layer prepared in Example 1 of the present invention.

[0050] Figure 3 The morphology diagram of the gradient W-Cr alloy layer prepared in Example 1 of the present invention and the corresponding element line scan distribution diagram. DETAILED DESCRIPTION

[0051] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0052] Embodiment 1:

[0053] A patterned high-reflection layer with good adhesion; the high-reflection layer comprises an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer, and a patterned reflective layer which are sequentially located on a surface-modified glass substrate from bottom to top;

[0054] Among them, the n(Si / W) layer is composed of n cycles of alternating deposition of Si layer and W layer, where the alternating cycle n is 30; the thickness of the Si layer is 3nm, and the thickness of the W layer is 3nm; the interface between the Si layer and the W layer is a wavy interface, and the average amplitude height of the wavy interface is 0.5nm, and the average width is 3.0nm; the bottom layer of the n(Si / W) layer is the Si layer and is connected to the surface modified glass substrate, and the top layer is the W layer.

[0055] The W content of the gradient W-Cr alloy layer gradually decreases and the Cr content gradually increases in the direction away from the n(Si / W) layer; the thickness of the gradient W-Cr alloy layer is 5nm. The thickness of the Cr layer is 20nm, the thickness of the silicon dioxide layer is 3nm, and the patterned reflective layer is CrON, and its thickness is 2nm.

[0056] The surface of the surface-modified glass substrate is a glass substrate surface-modified by oxygen plasma, and its average surface roughness is 0.15 nm.

[0057] The method for preparing a glass substrate surface modified by oxygen plasma comprises the following steps:

[0058] S1. Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol in sequence for 10 minutes each using an ultrasonic cleaner, and then dried completely in a vacuum drying oven at room temperature.

[0059] S2. Surface-modified glass substrate: The glass substrate is surface-modified by oxygen plasma to obtain an oxygen plasma surface-modified glass substrate; the process parameters of the oxygen plasma surface modification are: at a pressure of 1.0 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 50 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 70 W, and the sputtering time is 250 s.

[0060] This embodiment also provides a method for preparing a patterned high-reflective layer with good adhesion, comprising the following steps:

[0061] S1. Preparation of n (Si / W) layer: Using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of surface modified glass substrate, and the number of alternating deposition cycles is n to form n (Si / W) layer; the preparation parameters of Si layer are: Si with purity of 99.999% is used as target material, and high purity argon gas with purity of 99.999% is used as protective atmosphere, the argon flow rate is adjusted to 25sccm, the sputtering pressure is 0.15Pa, the sputtering power is 100w, the bias voltage is -50V, and the substrate temperature is 130℃. The preparation parameters of W layer are: W with purity of 99.999% is used as target material, and high purity argon gas with purity of 99.999% is used as protective atmosphere, the argon flow rate is adjusted to 35sccm, the sputtering pressure is 0.15Pa, the sputtering power is 200w, the bias voltage is -30V, and the substrate temperature is 150℃.

[0062] S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n(Si / W) layer; the preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is adopted, and a W target with a purity of 99.999% and a Cr target with a purity of 99.999% are used at the same time. Argon with a purity of 99.999% is used as the protective atmosphere, and the argon flow rate is adjusted to 25sccm. The initial sputtering power of the W target is 100w, and the sputtering power of the Cr target is 30w. The sputtering time is 5min. During the sputtering process, the sputtering power is adjusted every 30s. The power of the W target decreases linearly at a rate of 16w per minute, and the power of the Cr target increases linearly at a rate of 24w per minute. Finally, the sputtering power of the W target is 20w, and the sputtering power of the Cr target is 150w. During the sputtering process, the rotation speed is 20rpm, the sputtering temperature is 150℃, and the sputtering pressure is 4 mTorr.

[0063] S3. Preparation of Cr layer: A Cr layer is prepared on the gradient W-Cr alloy layer. The preparation parameters of the Cr layer are: magnetron sputtering method, 99.95% purity Cr as target material, 99.999% high purity argon gas with a flow rate of 30 sccm as atmosphere, sputtering power of 150 W, and deposition rate of 0.50 nm / s.

[0064] S4. Preparation of silicon dioxide layer: A silicon dioxide layer is prepared on the Cr layer. The preparation parameters of the silicon dioxide layer are: magnetron sputtering technology is used, quartz with a purity of 99.999% is used as the target material, a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% with a flow rate of 30sccm is used as the atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 300w, the sputtering pressure is 0.5Pa, the bias voltage is -50V, and the substrate temperature is 100℃.

[0065] S5. Preparation of a patterned reflective layer: A reflective layer to be patterned is prepared on a silicon dioxide layer by magnetron sputtering, and then a photoresist is coated and patterned on the reflective layer to be patterned, and then the reflective layer is etched by an etching solution to obtain a patterned reflective layer. The preparation parameters of the reflective layer to be patterned are: a magnetron sputtering method is used, Cr with a purity of 99.95% is used as a target material, and a mixed gas of argon gas with a purity of 99.999%, 99.999% high-purity nitrogen gas and 99.999% high-purity oxygen gas with a flow rate of 25sccm is used as an atmosphere, wherein the volume ratio of argon gas, nitrogen gas and oxygen gas is 4:1:1, and the sputtering power is 300w.

[0066] The present invention has effectively confirmed the effectiveness and uniqueness of its technical solution through a series of experimental results. Figure 1 The XRD phase analysis diagram of the surface modified glass substrate prepared in Example 1 and the n(Si / W) layer thereon is shown, which clearly shows the composition of the Si and W phases, confirming that the present invention successfully achieves the predetermined phase structure during the material preparation process. Figure 2 The wavy interface morphology of the n(Si / W) layer is presented. This unique interface structure not only verifies the innovation of the present invention in interface design, but also provides an intuitive structural basis for the performance optimization of the multilayer film. Figure 3 The morphology of the gradient W-Cr alloy layer and its corresponding element line scan distribution diagram clearly show the gradual decrease of W content and the gradual increase of Cr content from the n(Si / W) layer to the Cr layer. This gradient distribution feature strongly confirms the precise control capability of the present invention in achieving element gradient transition. These three groups of experimental results confirm each other and comprehensively demonstrate the outstanding achievements of the present invention in key technical points such as phase composition, interface structure design and element gradient control, providing strong experimental support for the scientificity and innovation of the technical solution of the present invention.

[0067] Embodiment 2:

[0068] A patterned high-reflection layer with good adhesion; the high-reflection layer comprises an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer and a patterned reflective layer which are sequentially located on a surface-modified glass substrate from bottom to top.

[0069] Among them, the n(Si / W) layer is composed of n cycles of alternating deposition of Si layer and W layer, where the alternating cycle n is 36; the thickness of the Si layer is 4.5nm, and the thickness of the W layer is 4.5nm; the interface between the Si layer and the W layer is a wavy interface, and the average amplitude height of the wavy interface is 0.8nm, and the average width is 3.8nm; the bottom layer of the n(Si / W) layer is the Si layer and is connected to the surface modified glass substrate, and the top layer is the W layer.

[0070] The W content of the gradient W-Cr alloy layer gradually decreases and the Cr content gradually increases in the direction away from the n(Si / W) layer; the thickness of the gradient W-Cr alloy layer is 8nm. The thickness of the Cr layer is 32nm, the thickness of the silicon dioxide layer is 5nm, and the reflective layer to be patterned is CrON, and its thickness is 5nm.

[0071] The surface-modified glass substrate of this embodiment is an oxygen plasma surface-modified glass substrate, and its average surface roughness is 0.24 nm.

[0072] The method for preparing a glass substrate surface modified by oxygen plasma comprises the following steps:

[0073] S1. Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol in sequence for 10 minutes each using an ultrasonic cleaner, and then dried completely in a vacuum drying oven at room temperature.

[0074] S2. Surface-modified glass substrate: The glass substrate is surface-modified by oxygen plasma to obtain an oxygen plasma surface-modified glass substrate; the process parameters of the oxygen plasma surface modification are: at a pressure of 1.3 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 59 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 73 W, and the sputtering time is 280 s.

[0075] This embodiment also provides a method for preparing a patterned high-reflective layer with good adhesion, comprising the following steps:

[0076] S1. Preparation of n (Si / W) layer: Using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of surface modified glass substrate, and the number of alternating deposition cycles is n to form n (Si / W) layer. The parameters for the preparation of Si layer are: Si with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 30sccm, the sputtering pressure is 0.21Pa, the sputtering power is 114w, the bias voltage is -60V, and the substrate temperature is 140℃. The parameters for the preparation of W layer are: W with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 40sccm, the sputtering pressure is 0.21Pa, the sputtering power is 245w, the bias voltage is -40V, and the substrate temperature is 160℃.

[0077] S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n(Si / W) layer. The preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is used, and a W target with a purity of 99.999% and a Cr target with a purity of 99.999% are used at the same time. Argon with a purity of 99.999% is used as the protective atmosphere. The argon flow rate is adjusted to 33sccm. The initial sputtering power of the W target is 115w, the sputtering power of the Cr target is 36w, and the sputtering time is 5min. During the sputtering process, the sputtering power is adjusted every 30s. The power of the W target decreases linearly at a rate of 17.2w per minute, and the power of the Cr target increases linearly at a rate of 25.8w per minute. Finally, the sputtering power of the W target is 29w, and the sputtering power of the Cr target is 165w. During the sputtering process, the rotation speed is 22rpm, the sputtering temperature is 160℃, and the sputtering pressure is 4 mTorr.

[0078] S3. Preparation of Cr layer: A Cr layer is prepared on the gradient W-Cr alloy layer. The preparation parameters of the Cr layer are: magnetron sputtering method, 99.95% purity Cr as target material, 99.999% high purity argon gas with a flow rate of 39 sccm as atmosphere, sputtering power of 165 W, and deposition rate of 0.62 nm / s.

[0079] S4. Preparation of silicon dioxide layer: A silicon dioxide layer is prepared on the Cr layer. The preparation parameters of the silicon dioxide layer are: magnetron sputtering technology is used, quartz with a purity of 99.999% is used as the target material, a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% at a flow rate of 39sccm is used as the atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 390w, the sputtering pressure is 0.8Pa, the bias voltage is -65V, and the substrate temperature is 115°C.

[0080] S5. Preparation of a patterned reflective layer: A reflective layer to be patterned is prepared on a silicon dioxide layer by magnetron sputtering, and then a photoresist is coated and patterned on the reflective layer to be patterned, and then the reflective layer is etched by an etching solution to obtain a patterned reflective layer. The preparation parameters of the reflective layer to be patterned are: magnetron sputtering is used, Cr with a purity of 99.95% is used as a target material, and a mixed gas of argon gas with a purity of 99.999%, 99.999% high-purity nitrogen gas and 99.999% high-purity oxygen gas with a flow rate of 33sccm is used as an atmosphere, wherein the volume ratio of argon gas, nitrogen gas and oxygen gas is 4:1:1, and the sputtering power is 390w.

[0081] Embodiment 3:

[0082] A patterned high-reflection layer with good adhesion; the high-reflection layer comprises an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer and a patterned reflective layer which are sequentially located on a surface-modified glass substrate from bottom to top.

[0083] Among them, the n(Si / W) layer is composed of n cycles of alternating deposition of Si layer and W layer, where the alternating cycle n is 42; the thickness of the Si layer is 6nm, and the thickness of the W layer is 6nm; the interface between the Si layer and the W layer is a wavy interface, and the average amplitude height of the wavy interface is 1.2nm, and the average width is 4.5nm; the bottom layer of the n(Si / W) layer is the Si layer and is connected to the surface modified glass substrate, and the top layer is the W layer.

[0084] The W content of the gradient W-Cr alloy layer gradually decreases and the Cr content gradually increases in the direction away from the n(Si / W) layer; the thickness of the gradient W-Cr alloy layer is 11nm. The thickness of the Cr layer is 44nm, the thickness of the silicon dioxide layer is 7nm, and the patterned reflective layer is CrON, and its thickness is 8nm.

[0085] The surface-modified glass substrate of this embodiment is an oxygen plasma surface-modified glass substrate, and its average surface roughness is 0.33 nm.

[0086] The method for preparing a glass substrate surface modified by oxygen plasma comprises the following steps:

[0087] S1. Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol in sequence for 10 minutes each using an ultrasonic cleaner, and then dried completely in a vacuum drying oven at room temperature.

[0088] S2. Surface-modified glass substrate: The glass substrate is surface-modified by oxygen plasma to obtain an oxygen plasma surface-modified glass substrate; the process parameters of the oxygen plasma surface modification are: at a pressure of 1.6 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 68 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 76 W, and the sputtering time is 310 s.

[0089] This embodiment also provides a method for preparing a patterned high-reflective layer with good adhesion, comprising the following steps:

[0090] S1. Preparation of n (Si / W) layer: Using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of surface modified glass substrate, and the number of alternating deposition cycles is n to form n (Si / W) layer. The parameters for the preparation of Si layer are: Si with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 34sccm, the sputtering pressure is 0.27Pa, the sputtering power is 127w, the bias voltage is -85V, and the substrate temperature is 150℃. The parameters for the preparation of W layer are: W with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 44sccm, the sputtering pressure is 0.27Pa, the sputtering power is 290w, the bias voltage is -70V, and the substrate temperature is 180℃.

[0091] S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n(Si / W) layer. The preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is used, and a W target with a purity of 99.999% and a Cr target with a purity of 99.999% are used at the same time. Argon with a purity of 99.999% is used as the protective atmosphere. The argon flow rate is adjusted to 40sccm. The initial sputtering power of the W target is 130w, the sputtering power of the Cr target is 42w, and the sputtering time is 5min. During the sputtering process, the sputtering power is adjusted every 30s. The power of the W target decreases linearly at a rate of 18.4w per minute, and the power of the Cr target increases linearly at a rate of 27.6w per minute. Finally, the sputtering power of the W target is 38w, and the sputtering power of the Cr target is 180w. During the sputtering process, the rotation speed is 25rpm, the sputtering temperature is 170℃, and the sputtering pressure is 4 mTorr.

[0092] S3. Preparation of Cr layer: A Cr layer is prepared on the gradient W-Cr alloy layer. The preparation parameters of the Cr layer are: magnetron sputtering method, 99.95% purity Cr as target material, 99.999% high purity argon gas with a flow rate of 48 sccm as atmosphere, sputtering power of 180 W, and deposition rate of 0.74 nm / s.

[0093] S4. Preparation of silicon dioxide layer: A silicon dioxide layer is prepared on the Cr layer. The preparation parameters of the silicon dioxide layer are: magnetron sputtering technology is used, quartz with a purity of 99.999% is used as the target material, a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% at a flow rate of 48sccm is used as the atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 480w, the sputtering pressure is 1.1Pa, the bias voltage is -80V, and the substrate temperature is 130°C.

[0094] S5. Preparation of a patterned reflective layer: A reflective layer to be patterned is prepared on a silicon dioxide layer by magnetron sputtering, and then a photoresist is coated and patterned on the reflective layer to be patterned, and then the reflective layer is etched by an etching solution to obtain a patterned reflective layer. The preparation parameters of the reflective layer to be patterned are: magnetron sputtering is used, Cr with a purity of 99.95% is used as a target material, and a mixed gas of 99.999% argon gas, 99.999% high-purity nitrogen gas, and 99.999% high-purity oxygen gas with a flow rate of 40sccm is used as an atmosphere, wherein the volume ratio of argon gas, nitrogen gas, and oxygen gas is 4:1:1, and the sputtering power is 480w.

[0095] Embodiment 4:

[0096] A patterned high-reflection layer with good adhesion; the high-reflection layer comprises an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer and a patterned reflective layer which are sequentially located on a surface-modified glass substrate from bottom to top.

[0097] Among them, the n(Si / W) layer is composed of n cycles of alternating deposition of Si layer and W layer, where the alternating cycle n is 50; the thickness of the Si layer is 8nm, and the thickness of the W layer is 8nm; the interface between the Si layer and the W layer is a wavy interface, and the average amplitude height of the wavy interface is 1.6nm, and the average width is 5.5nm; the bottom layer of the n(Si / W) layer is the Si layer and is connected to the surface modified glass substrate, and the top layer is the W layer.

[0098] The W content of the gradient W-Cr alloy layer gradually decreases and the Cr content gradually increases in the direction away from the n(Si / W) layer; the thickness of the gradient W-Cr alloy layer is 15nm. The thickness of the Cr layer is 60nm. The thickness of the silicon dioxide layer is 10nm, and the patterned reflective layer is CrON, and its thickness is 12nm.

[0099] The surface-modified glass substrate of this embodiment is an oxygen plasma surface-modified glass substrate, and its average surface roughness is 0.45 nm.

[0100] The preparation of the oxygen plasma surface modified glass substrate comprises the following steps:

[0101] S1. Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol for 10 minutes each in an ultrasonic cleaner by magnetron sputtering, and then dried completely in a vacuum drying oven at room temperature.

[0102] S2. Surface-modified glass substrate: The glass substrate is surface-modified by oxygen plasma to obtain an oxygen plasma surface-modified glass substrate; the process parameters of the oxygen plasma surface modification are: at a pressure of 2.0 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 80 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 80 W, and the sputtering time is 350 s.

[0103] This embodiment also provides a method for preparing a patterned high-reflective layer with good adhesion, comprising the following steps:

[0104] S1. Preparation of n (Si / W) layer: Using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of surface modified glass substrate, and the number of alternating deposition cycles is n to form n (Si / W) layer. The parameters for the preparation of Si layer are: Si with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 40sccm, the sputtering pressure is 0.35Pa, the sputtering power is 145w, the bias voltage is -100V, and the substrate temperature is 160℃. The parameters for the preparation of W layer are: W with a purity of 99.999% is used as the target material, high-purity argon gas with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 50sccm, the sputtering pressure is 0.35Pa, the sputtering power is 350w, the bias voltage is -80V, and the substrate temperature is 190℃.

[0105] S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n(Si / W) layer. The preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is used, and a W target with a purity of 99.999% and a Cr target with a purity of 99.999% are used at the same time. Argon with a purity of 99.999% is used as the protective atmosphere. The argon flow rate is adjusted to 50sccm. The initial sputtering power of the W target is 150w, the sputtering power of the Cr target is 50w, and the sputtering time is 5min. During the sputtering process, the sputtering power is adjusted every 30s. The power of the W target decreases linearly at a rate of 20w per minute, and the power of the Cr target increases linearly at a rate of 30w per minute. Finally, the sputtering power of the W target is 50w, and the sputtering power of the Cr target is 200w. During the sputtering process, the rotation speed is 30rpm, the sputtering temperature is 200℃, and the sputtering pressure is 4 mTorr.

[0106] S3. Preparation of Cr layer: A Cr layer is prepared on the gradient W-Cr alloy layer. The preparation parameters of the Cr layer are: magnetron sputtering method, 99.95% purity Cr as target material, 99.999% high purity argon gas with a flow rate of 60 sccm as atmosphere, sputtering power of 200 W, and deposition rate of 0.90 nm / s.

[0107] S4. Preparation of silicon dioxide layer: A silicon dioxide layer is prepared on the Cr layer. The preparation parameters of the silicon dioxide layer are: magnetron sputtering technology is used, quartz with a purity of 99.999% is used as the target material, a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% with a flow rate of 60sccm is used as the atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 600w, the sputtering pressure is 1.5Pa, the bias voltage is -100V, and the substrate temperature is 150°C.

[0108] S5. Preparation of a patterned reflective layer: A reflective layer to be patterned is prepared on a silicon dioxide layer by magnetron sputtering, and then a photoresist is coated and patterned on the reflective layer to be patterned, and then the reflective layer to be patterned is etched by an etching solution to obtain a patterned reflective layer. The preparation parameters of the reflective layer to be patterned are: magnetron sputtering is used, Cr with a purity of 99.95% is used as a target material, and a mixed gas of argon gas with a purity of 99.999%, 99.999% high-purity nitrogen gas and 99.999% high-purity oxygen gas with a flow rate of 50sccm is used as an atmosphere, wherein the volume ratio of argon gas, nitrogen gas and oxygen gas is 4:1:1, and the sputtering power is 600w.

[0109] Comparative Example 1

[0110] It is basically the same as Example 1, except that the glass substrate is not subjected to surface modification treatment, but a pre-treated glass substrate is used.

[0111] Comparative Example 2

[0112] It is basically the same as Example 1, except that the interface between the Si / W layers is a straight interface. The specific preparation parameters are as follows: Si with a purity of 99.999% is used as the target material, high-purity argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 25sccm, the sputtering pressure is 0.15Pa, and the sputtering power is 70w. The preparation parameters of the W layer are: W with a purity of 99.999% is used as the target material, high-purity argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 35sccm, the sputtering pressure is 0.15Pa, and the sputtering power is 120w. The sputtering power is reduced, the surface diffusion of the Si content is slowed down, and the surface migration of the W content is significantly reduced, which helps to form a straight interface.

[0113] Comparative Example 3

[0114] It is basically the same as Example 1, except that the W-Cr alloy layer is not designed with a gradient result, but a homogeneous material design, so the W-Cr alloy layer has no composition gradient change, and the specific preparation method is as follows: co-sputtering technology is adopted, and a W target with a purity of 99.999% and a Cr target with a purity of 99.999% are used at the same time, the sputtering power of the W target is 60w, the sputtering power of the Cr target is 80w, and the sputtering time is 6min. During the sputtering time, the power remains unchanged, the sputtering pressure is 4 mTorr, and the flow rate of argon gas with a purity of 99.999% is 25sccm. The W-Cr alloy layer is still designed to be 5nm.

[0115] Performance Test:

[0116] Adhesion test: The adhesion test was conducted using the WS-2005 coating adhesion automatic scratch tester. The instrument can continuously adjust the load in the range of 0-200N, and has constant load and incremental load test modes. During the test, the friction force and acoustic emission signals are monitored in real time to accurately determine the failure point of the coating. Multiple tests are performed at different locations on the sample to ensure the statistical significance of the results. The adhesion performance of the high reflective layer on the glass substrate is fully evaluated by analyzing the critical load, friction coefficient and failure mode. The test environment temperature and humidity are kept constant, and the sample surface needs to be clean and flat. After the test, the scratch track is observed with an optical microscope to deeply analyze the coating failure mechanism. This method can provide a comprehensive quantitative and qualitative evaluation of the adhesion of the high reflective layer.

[0117] Reflectivity: The reflectivity of the high reflective layer is tested using a Fourier spectrometer with a test band of 300-2500 nm, covering the visible light and near-infrared regions. The test uses a specular reflection accessory with an incident angle of 10° and a resolution better than 4 cm. -1 , each sample was scanned at least 32 times to improve the signal-to-noise ratio. During the test, the ambient temperature and humidity must be controlled, the instrument must be calibrated regularly, and the uniformity and polarization sensitivity of the sample must be considered.

[0118] Internal stress: The internal stress of the high reflective layer was tested by X-ray stress determination, and the measurement was performed using an X-ray diffractometer. The test used a Cu Kα radiation source (wavelength 1.5406 Å) with a scanning range of 2θ = 20°-80°. The sin²ψ method was used to calculate the stress by measuring the change in the interplanar spacing at different tilt angles ψ. The test parameters were: tube voltage 40 kV, tube current 40 mA, step length 0.02°, and counting time of 2 seconds per step. At least 5 different ψ angles (in the range of 0°-60°) were selected for measurement. The data analysis used a linear regression method to calculate the residual stress based on the slope of the d-sin²ψ graph. The test should pay attention to the surface cleanliness of the sample, consider the texture effect, and measure in different orientations to evaluate the anisotropy of stress.

[0119] The properties of the high reflective layers of Examples 1 to 7 and Comparative Examples 1 to 3 are summarized in Table 1.

[0120] Table 1 Performance of high reflective layer of Examples 1 to 7 and Comparative Examples 1 to 3

[0121] As can be seen from Table 1, the main difference between Comparative Example 1 and Example 1 is the treatment method of the glass substrate. Example 1 adopts surface modification treatment, while Comparative Example 1 only uses a pre-treated glass substrate. As can be seen from Table 1, Example 1 can significantly improve the adhesion and internal stress tolerance of the coating, while slightly improving the reflectivity. This is because the surface modification treatment can increase the roughness and active sites on the surface of the glass substrate, thereby enhancing the mechanical locking and chemical bonding between the coating and the substrate. The modification treatment may also optimize the stress distribution of the coating and improve the coating's tolerance to internal stress. In terms of reflectivity, the surface after the modification treatment may be more conducive to forming a uniform and dense coating structure, thereby slightly improving the optical performance.

[0122] The main difference between Comparative Example 2 and Example 1 lies in the interface morphology between the Si / W layers. Example 1 adopts a wavy interface, while Comparative Example 2 is a straight interface. As can be seen from Table 1, Example 1 can significantly improve the adhesion and internal stress tolerance of the coating, and may slightly improve the reflectivity. This is because the wavy interface increases the interlayer connection area, improves the mechanical interlocking effect, and thus enhances the interlayer bonding force. The wavy interface can also better disperse and release stress and improve the internal stress tolerance of the coating. In terms of reflectivity, the wavy interface may help reduce interface scattering and absorption, thereby slightly improving the reflection efficiency of light, but this effect may not be as significant as other factors.

[0123] In summary, the present invention achieves the combination of high reflective performance and good adhesion through innovative technologies such as oxygen plasma surface modification, wavy interface design, gradient alloy transition and patterned reflective layer, solving the problems of easy peeling and poor stability of traditional high reflective layers.

[0124] The main difference between Comparative Example 3 and Example 1 lies in the structural design of the W-Cr alloy layer. Example 1 adopts a gradient structure design, while Comparative Example 3 uses a homogeneous material design. As can be seen from Table 1, Example 1 can significantly improve the adhesion and internal stress tolerance of the coating, while the reflectivity is slightly improved. This is because the gradient structure design can achieve a gradual transition of the coating composition and performance, reduce interface stress concentration, and improve the bonding between the coating and the substrate and between the layers. The gradient structure can also optimize the stress distribution and improve the internal stress tolerance of the coating. In terms of reflectivity, the gradient structure may slightly improve the reflection efficiency by reducing interface scattering, but this effect may not be as significant as other factors.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A patterned high-reflective layer with good adhesion, characterized in that: The high reflective layer includes an n(Si / W) layer, a gradient W-Cr alloy layer, a Cr layer, a silicon dioxide layer, and a patterned reflective layer, which are sequentially located on the surface-modified glass substrate from bottom to top; The n(Si / W) layer is composed of n cycles of alternate deposition of Si layer and W layer, wherein the alternating cycle n is 30-50; the bottom layer of the n(Si / W) layer is a Si layer connected to the surface-modified glass substrate, and the top layer is a W layer; the thickness of the Si layer is 3-8 nm, the thickness of the W layer is 3-8 nm, and the thickness ratio of the Si layer to the W layer is 1:1; the interface between the Si layer and the W layer is a wavy interface; The gradient W-Cr alloy layer has a W content that gradually decreases and a Cr content that gradually increases in a direction away from the n(Si / W) layer; The surface-modified glass substrate is an oxygen plasma surface-modified glass substrate; the average surface roughness of the oxygen plasma surface-modified glass substrate is 0.15-0.45 nm; The method for surface modification of a glass substrate by oxygen plasma comprises the following steps: 1) Pretreatment of glass substrate: The glass substrate was cleaned in acetone and isopropanol in sequence using an ultrasonic cleaner, and then dried completely in a vacuum drying oven at room temperature; 2) Surface modification of glass substrate: The glass substrate obtained by step 1) is surface modified by oxygen plasma; the process parameters of the oxygen plasma surface modification are: at a pressure of 1.0-2.0 Pa, in a mixed atmosphere of argon and oxygen with a flow rate of 50-80 sccm, wherein the volume ratio of argon to oxygen is 1:4, the sputtering power is 70-80 W, and the sputtering time is 250-350 s.

2. The patterned high-reflective layer with good adhesion as claimed in claim 1, characterized in that: The average amplitude height of the wavy interface is 0.5-1.6 nm, and the average width is 3.0-5.5 nm.

3. The patterned high-reflective layer with good adhesion as claimed in claim 1, characterized in that: The thickness of the gradient W-Cr alloy layer is 5-15 nm; The thickness of the Cr layer is 20-60 nm; The thickness of the silicon dioxide layer is 3 to 10 nm; The patterned reflective layer is CrON, and its thickness is 2-12 nm.

4. The method for preparing a patterned high-reflective layer with good adhesion as claimed in any one of claims 1 to 3, comprising the following steps: S1. Preparation of n (Si / W) layer: using magnetron sputtering method, Si layer and W layer are alternately deposited on the surface of the surface modified glass substrate, the number of alternating deposition cycles is n, and n (Si / W) layer is formed; The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% is used as the target material, argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 25-40 sccm, the sputtering pressure is 0.15 Pa-0.35 Pa, the sputtering power is 100-145 W, the bias voltage is -50--100 V, and the substrate temperature is 130-160 ° C. The preparation parameters of the W layer are as follows: W with a purity of 99.999% is used as the target material, argon with a purity of 99.999% is used as the protective atmosphere, the argon flow rate is adjusted to 35~50sccm, the sputtering pressure is 0.15~0.35Pa, the sputtering power is 200~350w, the bias voltage is -30~-80V, and the substrate temperature is 150~190℃; S2. Preparation of gradient W-Cr alloy layer: magnetron sputtering gradient W-Cr alloy layer on the surface of n (Si / W) layer; Preparation parameters of the gradient W-Cr alloy layer are as follows: magnetron co-sputtering technology is adopted, a W target material with a purity of 99.999% and a Cr target material with a purity of 99.999% are used simultaneously, argon gas with a purity of 99.999% is used as a protective atmosphere, the argon gas flow rate is adjusted to 25-50 sccm, the initial sputtering power of the W target material is 100-150w, the sputtering power of the Cr target material is 30-50w, and the sputtering time is 5min. During the sputtering process, the sputtering power is adjusted once every 30s, the power of the W target material decreases linearly at a rate of 16-20w per minute, and the power of the Cr target material increases linearly at a rate of 24-30w per minute. Finally, the sputtering power of the W target material is 20-50w, and the sputtering power of the Cr target material is 150-200w. During the sputtering process, the rotation speed is 20-30rpm, the sputtering temperature is 150-200℃, and the sputtering pressure is 4 mTorr; S3. Preparation of Cr layer: Preparing a Cr layer on a gradient W-Cr alloy layer; S4. Preparing a silicon dioxide layer: Preparing a silicon dioxide layer on the Cr layer; S5. Preparing a patterned reflective layer: using a magnetron sputtering method to prepare a reflective layer to be patterned on the silicon dioxide layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer.

5. The method for preparing a patterned high-reflective layer with good adhesion as claimed in claim 4, characterized in that: The preparation parameters of the Cr layer in step S3 are: magnetron sputtering method, Cr with a purity of 99.95% as the target material, 99.999% argon gas with a flow rate of 30-60 sccm as the atmosphere, sputtering power of 150-200w; deposition rate of 0.50-0.90 nm / s; The preparation parameters of the silicon dioxide layer in step S4 are: using magnetron sputtering technology, using quartz with a purity of 99.999% as the target material, using a mixture of argon with a purity of 99.999% and oxygen with a purity of 99.999% at a flow rate of 30-60 sccm as the atmosphere, wherein the volume ratio of argon to oxygen is 4:1, the sputtering power is 300-600w, the sputtering pressure is 0.5-1.5Pa, the bias voltage is -50--100V, and the substrate temperature is 100-150°C; The preparation parameters of the reflective layer to be patterned in step S5 are: magnetron sputtering method, Cr with a purity of 99.95% is used as the target material, and a mixed gas of 99.999% argon, 99.999% nitrogen and 99.999% oxygen with a flow rate of 25~50sccm is used as the atmosphere, wherein the volume ratio of argon, nitrogen and oxygen is 4:1:1, and the sputtering power is 300~600w.

6. Use of the high reflective layer according to any one of claims 1 to 3 or the high reflective layer prepared by the preparation method according to any one of claims 4 to 5 in the field of photolithography mask, optical system or semiconductor manufacturing.

Citation Information

Patent Citations

  • EUV photomask and manufacturing method thereof

    CN113267956A

  • WC hard alloy thin film and gradient layer technology room temperature preparation method thereof

    CN108149198A

  • Metal-dielectric type spectral selectivity multiband stealth film and preparation method thereof

    CN112346162A

  • Single-sided patterned high-low reflective film layer and preparation method and application thereof

    CN118131379A

  • Aviation blade cutting tool

    CN204867476U